School Curriculum of Technology in Primary Schools in Slovakia – A Case Study - Lukáčová, Danka (The University of Rzeszów Publishing House, 2023)
Since 2008, schools in Slovakia have been able to adapt the curriculum of each subject according to the requirements of the school, pupils or parents. Only the content and performance standards of the subject are binding for them. In this article, we publish an analysis of three school curricula and thematic educational plans. Through content analysis of the documents, we investigated how primary schools implement the content of the subject of technology. We analysed the differences in the thematic units, common features and the number of lessons each topic implements. We found differences in the thematic units that primary school teachers include in teaching technology, although they are insignificant. We identified the most considerable differences in the seventh year of primary school. Also, the thematic units taught in the subject area of Household economics are very heterogeneous in schools.
Keywords: school curriculum; thematic curriculum; content standard; content analysis; technology